"Stellar Prominences" on OB starsto explain wind-line variability. Issue Volume 9:Issue S302(2013) (7th August 2014) - Henrichs, H. F.; Sudnik, N. P.
Abstract: Many O and B stars show unexplained cyclical variability in their winds, i.e. modulation of absorption features on the rotational timescale, but not strictly periodic over longer timescales. For these stars no dipolar magnetic fields have been detected, with upper limits below 300 G. Similar cyclical variability is also found in many optical lines, which are formed at the base of the wind. We propose that these cyclical variations are caused by the presence of multiple, transient, short-lived, corotating magnetic loops, which we call "stellar prominences". We present a simplified model representing these prominences to explain the cyclical optical wind-line variability in the O supergiant λ Cephei. Other supporting evidence for such prominences comes from the recent discovery of photometric variability in a comparable O star, which was explained by the presence of multiple transient bright spots, presumably of magnetic origin as well.